Genetic differentiation of parthenogenetic lizards Darevskia rostombekowi (Family Lacertidae) as determined using nuclear and mitochondrial DNA markers - Malysheva, D. N.; Tokarskaya, O. N.; Petrosyan, V. G.; Danielyan, F. D.; Darevskii, I. S.; Ryskov, A. P. (Doklady. Biochemistry and biophysics, 2006)
(ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT]